The antipsychotic activity of alcoholic extract of Withania coagulans fruits in Swiss albino mice - Kamdi, Amit S.; Kokane, Sarika D.; Bohra, Pankaj N.; Kalambe, Suvarna M. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Schizophrenia is one of the most distressing central nervous system (CNS) disorders. It is described by positive, negative and cognitive symptoms. These symptoms can be controlled by the antipsychotic medicines. The numerous antipsychotic medications used today are not lacking the adverse drug reactions. The Withania coagulans a susceptible species, is not explored much for its CNS effects except in late seventies. Therefore, it was thought worthwhile to investigate anti-psychotic activities of alcoholic extract of Withania coagulans fruits. The objective of the present study was to assess the antipsychotic activity of alcoholic extract of Withania coagulans fruits in Swiss albino mice by Cook’s Pole Climb Apparatus for conditioned avoidance response (CAR) Methods: Cook’s Pole Climb Apparatus for conditioned avoidance response was used for assessing the antipsychotic activity of the alcoholic extract of 200mg/kg, 500mg/kg and 1000mg/kg doses of Withania coagulans fruits. Results: There was statistically (p-value >0.05) no significant association between any of the 200mg/kg, 500mg/kg and 1000mg/kg doses of the alcoholic extracts of Withania coagulans fruits with antipsychotic activity in Swiss albino mice. Conclusions: Withania coagulans fruits alcoholic extract did not demonstrate antipsychotic activity in Swiss albino mice under standard conditions.